Effects of melatonin on cognitive impairment and hippocampal neuronal damage in a rat model of chronic cerebral hypoperfusion - LEE, CHOONG HYUN (Exp Ther Med, 2016)
Chronic cerebral hypoperfusion (CCH), which induces oxidative stress and inflammation in the brain, has previously been associated with cognitive impairment and neuronal cell damage. Melatonin is a well-known free radical scavenger and antioxidant; therefore, the present study investigated the protective effects of melatonin against CCH-induced cognitive impairment and neuronal cell death in a CCH rat model, which was generated via permanent bilateral common carotid artery occlusion (2VO). The rats in the 2VO group exhibited markedly increased escape latencies in a Morris water maze test, as compared with the rats in the sham group. In addition, increased neuronal cell damage was detected in the hippocampal CA1 region of the 2VO rats, as compared with the rats in the sham group. Treatment of the 2VO rats with melatonin significantly reduced the escape latency and neuronal cell damage, and was associated with reduced levels of malondialdehyde, microglial activation, and tumor necrosis factor-α and interleukin-1β in the ischemic hippocampus. The results of the present study suggest that melatonin may attenuate CCH-induced cognitive impairment and hippocampal neuronal cell damage by decreasing oxidative stress, microglial activation and the production of pro-inflammatory cytokines in the ischemic hippocampus.